Pengaruh Disiplin Kerja, Stres Kerja dan Perceived Organizational Support Terhadap Kinerja Karyawan PT Taruna Bima Abadi Karanganyar - Putuwijayanti, Retno; Sutarno (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study is intended to evaluate the impact of work discipline, work stress, and perceived organisational support on employee performance. The study was conducted using a census approach involving 68 respondents. Data was collected through questionnaires that were tested for validity and reliability. Data analysis was applied using multiple linear regression, t test, F test, and coefficient of determination testing. The results of the analysis show that work discipline has a positive and significant influence on employee performance. In contrast, job stress showed a negative but insignificant influence on employee performance. Perceived organisational support was also found to have a positive and significant influence on employee performance. The F test shows that the significance value (p value) is 0.000 <0.05, which indicates that the model used is suitable for predicting the effect of work discipline, work stress, and perceived organisational support on employee performance at PT Taruna Bima Abadi Karanganyar. The coefficient of determination obtained is 0.290, indicating that 29% of the variation in employee performance at PT Taruna Bima Abadi Karanganyar can be explained by the variables of work discipline, work stress, and perceived organisational support, while the remaining 71% is influenced by other variables not included in this study